EXPLICIT INSTRUCTION: A METHOD TO ENGAGE STUDENTS IN ENGLISH AS A FOREIGN LANGUAGE (EFL) SOURCE-BASED WRITING - Maulidiyah, Noor (STKIP Persada Khatulistiwa Sintang, 2024)
Academic writing is a crucial subject for university students to equip them with the necessary skills for writing academic research papers. However, writing is a particularly complex skill for a second language and foreign language learners to learn. University students may lack background knowledge about English writing, particularly writing based on sources. Source-based writing is a fundamental academic writing skill in universities. It includes the skills of paraphrasing, summarizing, and synthesizing. English as a Foreign Language (EFL) learners may face difficulties in producing such writing which could lead to higher practices of plagiarism and academic misconduct. These practices of plagiarism and academic misconduct could be minimized by explicit instruction on source-based writing in Academic Writing courses. This paper argues that explicit instruction is an effective method for teaching source-based writing. The paper aims to explore the concept of explicit instruction in teaching and learning EFL source-based writing. The writer utilized qualitative secondary research and reviewed 15 relevant sources published between 2014 and 2024. Through this qualitative secondary research which is a form of library research, the notion of explicit reading and writing instructions is investigated. Furthermore, this paper explores strategies that can be employed in teaching source-based using explicit instruction in Indonesian tertiary-level EFL classrooms. The paper also highlights the challenges in implementing explicit instruction. This method of explicit reading and writing instructions should provide practical implications for teaching source-based writing. Keywords: academic writing; explicit instruction; source-based writing; paraphrasing; summarizing; synthesizing